Is every other day iron supplementation effective for the treatment of the iron deficiency anemia in pregnancy?. (4th March 2022) - Karakoc, Gokhan; Orgul, Gokcen; Sahin, Dilek; Yucel, Aykan
Abstract: Aim: To understand if every other day iron supplementation may be as effective as daily iron intake in anemic pregnant women. Methods: This case-control study was conducted at a tertiary hospital in Turkey. The study randomly categorized women into two groups as daily intake ( n  = 124) vs every other day intake ( n  = 140) of 100 mg daily oral ferrous fumarate. The numbers of women recruited from the study were 13 and 34 in two groups. Thus, for analysis, there were 111 women in the daily group and 106 women in the other group. The current study obtained hemoglobin (Hb) and ferritin levels two times to evaluate the effects of treatment, noting initial levels before drug administration, and a second blood sample was obtained after two months. Two groups were compared according to the increase in Hb and ferritin levels. The study asked the women whether they experienced gastrointestinal side effects. Results: The ferritin levels increased 4.9 ± 4.2 ng/mL in the daily intake group and 3.9 ± 2.9 ng/mL in every other day group ( p  = .215). The Hb increased 1.4 ± 0.7 g/dL in the daily intake group and 1.6 ± 0.6 g/dL in the other group ( p  = .021). Gastrointestinal side effects appeared in 47 (17.8%) out of 264 women. The rate of gastrointestinal side effect was lower in every other day group (41.4% vs 15.1%, p  = .0057). Conclusion: Every other day iron supplementation is as effective as daily intake for treating iron deficiency anemia with lesser gastrointestinal side effects during pregnancy.